Blood transcriptomics identifies immune signatures indicative of infectious complications in childhood cancer patients with febrile neutropenia. Issue 5 (17th May 2022) - Haeusler, Gabrielle M; Garnham, Alexandra L; Li‐Wai‐Suen, Connie SN; Clark, Julia E; Babl, Franz E; Allaway, Zoe; Slavin, Monica A; Mechinaud, Francoise; Smyth, Gordon K; Phillips, Bob; Thursky, Karin A; Pellegrini, Marc; et al.
Abstract: Objectives: Febrile neutropenia (FN) is a major cause of treatment disruption and unplanned hospitalization in childhood cancer patients. This study investigated the transcriptome of peripheral blood mononuclear cells (PBMCs) in children with cancer and FN to identify potential predictors of serious infection. Methods: Whole‐genome transcriptional profiling was conducted on PBMCs collected during episodes of FN in children with cancer at presentation to the hospital (Day 1; n  = 73) and within 8–24 h (Day 2; n  = 28) after admission. Differentially expressed genes as well as gene pathways that correlated with clinical outcomes were defined for different infectious outcomes. Results: Global differences in gene expression associated with specific immune responses in children with FN and documented infection, compared to episodes without documented infection, were identified at admission. These differences resolved over the subsequent 8–24 h. Distinct gene signatures specific for bacteraemia were identified both at admission and on Day 2. Differences in gene signatures between episodes with bacteraemia and episodes with bacterial infection, viral infection and clinically defined infection were also observed. Only subtle differences in gene expression profiles between non‐bloodstream bacterial and viral infections were identified. Conclusion: Blood transcriptome immune profiling analysis during FN episodes may inform monitoring and aid in defining adequate treatment for different infectious aetiologies in children with cancer. Abstract : We successfully demonstrate that blood transcriptomic analyses in children with cancer who develop febrile neutropenia may have utility in predicting the cause of fever and in identifying serious infectious complications. This can inform monitoring and aid in defining adequate treatment for different infectious aetiologies in childhood cancer patients.